PENGARUH LITERASI KEUANGAN TERHADAP INKLUSI KEUANGAN MAHASISWA PROGRAM STUDI S1 AKUNTANSI UNIVERSITAS MATARAM - RIKA SALSABILA PUTRI; NINA KARINA KARIM (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to determine the influence of financial literacy on the financial inclusion of students in the Bachelor of Accounting Study Program at Mataram University. This research uses an associative quantitative approach. In this study, measuring financial literacy used two approaches, namely objective test measures/objective financial literacy and subjective evaluation measures/subjective financial literacy. The sample used in this research was 168 Bachelor of Accounting students from the University of Mataram Class of 2022. The results of the research showed that the financial literacy variable with an objective approach had no significant effect on accounting students' financial inclusion, while the financial literacy variable with a subjective approach had a positive and significant effect on financial inclusion. accounting student